If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -4 + 8x + 3 = 32 Reorder the terms: -4 + 3 + 3x + 8x = 32 Combine like terms: -4 + 3 = -1 -1 + 3x + 8x = 32 Combine like terms: 3x + 8x = 11x -1 + 11x = 32 Solving -1 + 11x = 32 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 11x = 32 + 1 Combine like terms: -1 + 1 = 0 0 + 11x = 32 + 1 11x = 32 + 1 Combine like terms: 32 + 1 = 33 11x = 33 Divide each side by '11'. x = 3 Simplifying x = 3
| -9(-7)= | | 4y-4+y+24=6y+20-4y | | x^2-14x-4=0 | | 5(2x+8)=-14+44 | | xy-y^2=2-3x^3+x | | 8z^3-64=0 | | 10(2n+1)-6=20(n-1)+12 | | X+13= | | 4x-3=3x+7 | | 10-(4y-8)=4-5y | | w^2+18w+56= | | 16(x-5)=-8-8 | | 6(7+y)=5(y-1) | | x^2=6x-4graph | | 9x+4x+3+8=5x+3+7x | | 2(x-6)-(9+4x)=-3x | | x^2=6x-4 | | (4-32)0.56=c | | 0.4(a+20)=6 | | 3(x+3)=2+2x | | 4x+11=31 | | 9(z-5)=8z | | -r-4=4-5r | | 4x^2+3x-3=0 | | X-10=42 | | -7(x-1)=1-6x | | 2-4(y-5)=-4 | | (110-32)0.56= | | 8x^3=392x | | 50x^2+12=15 | | 8-2q=4 | | 0.7x-0.4x-6=-3 |